Transcriptomics explores the potential of flavonoid in non-medicinal parts of Saposhnikovia divaricata (Turcz.) Schischk - Chen, Yuqiu; Zhang, Tao; Chen, Changbao; Xu, Zhefeng; Liu, Chunshuo (Frontiers in Plant Science, 2023)
Saposhnikovia divaricata is a traditional Chinese medicine in China, which is widely used in clinic. The root of S. divaricata is often used as medicine, but little research has been done on its other tissues. In this study, the contents of root and leaf of S. divaricata were determined by HPLC, the differentially expressed genes were screened by transcriptome sequencing at molecular level, and then verified by network pharmacology. The results showed that the content of 4’-O-β-D-glucosyl-5-O-methylvisamminol in the leaves was significantly higher than that in the roots, which was about 3 times higher than that in the roots. In addition, 10 differentially expressed key enzyme genes were screened in plant hormone signal transduction, phenylpropanoid and flavonoid biosynthetic pathways. C4H and CYP98A were up-regulated in root, while F3H was down-regulated in root. They can be used as important candidate genes for the mechanism of quality difference of S. divaricata. Finally, network pharmacological validation showed that 5-O-methylvesamitol plays an important role in the treatment of ulcerative colitis. If some methods can be taken to convert 4’-O-β-D-glucosyl-5-O-methylvisamminol into 5-O-methylvesamitol which is easily absorbed by human body, the leaves of S. divaricata will have great development and utilization value. These ﬁndings not only provide insight into ﬂavonoid biosynthesis in S. divaricata associated molecular regulation, but also provide a theoretical basis for the development and utilization of S. divaricata.